Ultrafine grain tungsten-based composite material and preparation method thereof
By introducing rhenium and graphene into ultrafine grain tungsten material and coordinating with methyl 3-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione, an ultrafine grain tungsten-based composite material with high efficiency self-healing properties was prepared, solving the problem of recrystallization brittleness during the cooling process.
Patent Information
- Application Number
- CN202411899537.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The existing ultrafine grain tungsten materials are prone to recrystallization brittleness during cooling, which limits their widespread use in various applications.
Rhenium and graphene are used as auxiliary materials, and ultrafine grain tungsten-based alloys are prepared through high-precision pressing technology, high-value plastic deformation technology and high-pressure sintering technology. Using ethyl acetoacetate as the starting material, methyl 3-5-(1,8-naphthyridine-2-yl)-2H-pyrrole-2,4(3H)-dione is synthesized through esterification, Knoevenagel condensation and other reactions, and coordinated with the ultrafine grain tungsten-based alloy. Through catalysis and polymerization, an ultrafine grain tungsten-based composite material with high efficiency self-healing properties is obtained.
The efficient self-repair performance of ultrafine grain tungsten-based composite materials is achieved. Through supramolecular interaction mechanisms such as dynamic bonds and ion interactions, the material can be repaired automatically after mechanical damage.
Smart Images

Figure CN119708525A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ultrafine grain tungsten-based composite materials, and in particular to an ultrafine grain tungsten-based polymer composite material and a preparation method thereof. Background Art
[0002] Tungsten metal is a naturally occurring rare metal, known for its extremely high melting point. Tungsten is a brittle metal at room temperature, lacks ductility, and has a high ductile-brittle transition temperature, so it is difficult to plastically deform in the solid state, which hinders the application of tungsten in many fields.
[0003] Relevant literature records that forming ultrafine grains and nano-grain structures is a potential method to improve the ductility of tungsten and reduce the ductile-brittle transition temperature. This is because the high volume fraction of grain boundaries in the UFG microstructure can change the deformation mechanism of the metal. The ductile-brittle transition temperature of ultrafine-grained tungsten with an average grain size of 0.44μm is significantly reduced. At the same time, in ultrafine-grained polycrystalline materials, increasing the grain boundary area and reducing the average impurity concentration at the grain boundaries can improve the strength and toughness of tungsten.
[0004] Ultrafine grain tungsten-based materials refer to tungsten-based alloys or complexes with a grain size of less than 1μm. Through special preparation methods, the grain size can even reach the nanometer level. At present, the preparation methods of ultrafine grain tungsten-based materials include powder metallurgy / casting, sol-gel, wet chemical, high-value plastic deformation technology, high-pressure torsion, deformation drive technology, etc. Powder metallurgy / casting is easy to introduce impurities. Although the grains prepared by the sol-gel method are of higher purity and finer grain powder, the reaction conditions are strict, the process cycle is long, and the cost is high. The wet chemical method has relatively low cost and high batch production efficiency, but it will produce harmful gases and high reagent consumption. High-value plastic deformation technology requires the use of special molds, which are expensive, bulky, energy-consuming, and noisy, and it is impossible to expand the scale of production. High-pressure torsion and deformation drive technology can not only overcome the defects of other technologies, but also prepare ultrafine grain tungsten with complex geometric shapes.
[0005] Researchers have found that the brittleness of metal tungsten has been improved to a certain extent after ultrafine grain tungsten or nano-grain tungsten is prepared, but it has not achieved the expected effect because tungsten produces recrystallization brittleness during the cooling process. In the prior art, ultrafine grain tungsten / oxide is prepared by doping metal tungsten with other metal oxides, metal elements or nanographene. Compared with tungsten, it has stronger mechanical properties, stability, ductility and manufacturability because the doping substance can inhibit the recrystallization of tungsten during high-temperature cooling, control the growth rate and direction of the grains, and hinder grain boundary sliding.
[0006] The Chinese patent with publication number CN 107326240A discloses a tungsten-based composite material prepared by using TiC and Y2O3 as auxiliary materials and combining spark plasma sintering technology, which effectively refines the grains and improves the sintering performance and mechanical properties of tungsten materials. The Chinese patent with publication number CN 1775425 A discloses a copper powder-doped ultrafine-grained tungsten with controllable grain size, which is pressed by powder casting and then sintered with 10-25kW AC under a high pressure of 1-10GPa. The prepared ultrafine-grained tungsten-based block has good mechanical properties and thermal shock resistance. However, ultrafine-grained tungsten is mostly used in the forging of wear-resistant parts and high-temperature components, as well as in aerospace and military fields; there is still little research on composite materials of ultrafine-grained tungsten-based and polymer coordination, but the ionic interaction, π-π stacking, metal-ligand interaction, etc. in its structure have high research value in self-repair and sensing. Therefore, it is particularly important to provide a composite material of ultrafine-grained tungsten-based and polymer-coordinated with self-repairing ability. Summary of the invention
[0007] The present invention aims to provide an ultrafine-grained tungsten-based composite material and a preparation method thereof. The present invention uses rhenium and graphene as auxiliary materials, and obtains an ultrafine-grained tungsten-based alloy through high-precision pressing technology, high-value plastic deformation technology, and high-pressure sintering; uses ethyl acetoacetate as a starting raw material, synthesizes methyl 3-5-(1,8-naphthyridine-2-yl)-2H-pyrrole-2,4(3H)-dione through esterification, Knoevenagel condensation, etc., coordinates with an ultrafine-grained tungsten-based alloy, and obtains an ultrafine-grained tungsten-based composite material with high-efficiency self-repairing performance through catalysis and polymerization.
[0008] In order to achieve the above object, the present invention provides an ultrafine grain tungsten-based composite material, the structural formula of which is as follows:
[0009]
[0010] In the structure, α is an integer between 1 and 10, β is an integer between 1 and 10, and n is an integer between 2 and 12.
[0011] The present invention also provides a method for preparing an ultrafine grain tungsten-based composite material, comprising:
[0012]
[0013] Using ethyl acetoacetate as the starting material, mix it with sodium nitrate and acetic acid, and react at 115-120°C for 6-8h to obtain ethyl acetoacetate;
[0014] 2-nitro-ethyl acetoacetate is mixed with zinc powder, propionic anhydride and acetic acid, and reacted at 115-120°C for 8-10 hours to obtain a crude product of ethyl 3-oxo-2-propionamidobutyrate, and a pure product is obtained after recrystallization;
[0015] 3-Oxo-2-propionamidobutyric acid ethyl ester is mixed with 2-aminonicotinaldehyde, pyrrolidine and anhydrous ethanol, and reacted at 70-80°C for 12-14 hours to obtain a crude product of 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionic acid methyl ester, and a pure product is obtained by column chromatography;
[0016] 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionic acid methyl ester is mixed with titanium tetrachloride, triethylsilane and dichloromethane, and reacted at 25-40° C. for 10-12 hours to obtain a crude product of 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione, the solvent is removed, and the product is dried and recrystallized to obtain a pure product;
[0017] 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione is mixed with anhydrous lithium chloride, ultrafine grain rhenium-tungsten / graphene, and N,N-dimethylformamide, and reacted at 150-160° C. for 8-10 hours. Acetone is added to the system, and the system is refrigerated overnight below 0° C. to wait for crystals to precipitate, thereby obtaining a crude product of 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione / tungsten complex, which is then washed to obtain a pure product.
[0018] The tungsten complex was mixed with 2,11-dimethyldodecane-3,10-diol, triphenylphosphine, 2,2'-di(diethylamino)diethylphosphine and tetrahydrofuran, and reacted at room temperature for 12 hours. The obtained high molecular polymer was washed to obtain a tungsten-based composite material.
[0019] Preferably, the mass ratio of ethyl acetoacetate, sodium nitrate and acetic acid is 1:(1.3-1.4):(2-3).
[0020] Preferably, the mass ratio of the 2-nitro-ethyl acetoacetate to the zinc powder, propionic anhydride and acetic acid is 1:(0.3-1):(0.7-0.8):(2-3).
[0021] Preferably, the recrystallization reagent is any one or more of ethanol, methanol, ethyl acetate, dichloromethane, ether, and chloroform.
[0022] Preferably, the mass ratio of ethyl 3-oxo-2-propionamidobutyrate to 2-aminonicotinaldehyde, pyrrolidine and anhydrous ethanol is 1:(0.6-0.7):(0.025-0.034):(1.5-1.6).
[0023] Preferably, the mobile phase used in the column chromatography is a system of dichloromethane and methanol, and the volume ratio of the two is 20:1.
[0024] Preferably, the mass ratio of the 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionic acid methyl ester to titanium tetrachloride, triethylsilane and dichloromethane is 1:(0.6-0.7):(0.06-0.3):(2.6-3).
[0025] Preferably, the recrystallization solvent is any one or more of ethanol, methanol, ethyl acetate and acetone.
[0026] Preferably, the mass ratio of the 3-methyl-5-(1,8-naphthyridine-2-yl)-2H-pyrrole-2,4(3H)-dione to LiCl, ultrafine grain rhenium-tungsten / graphene, and N,N-dimethylformamide is 1:(0.17-0.18):(0.75-0.78):(4-5).
[0027] Preferably, the method for preparing ultrafine grain rhenium-tungsten / graphene powder comprises:
[0028] The tungsten powder and rhenium powder are mixed evenly, and rhenium-doped nano-tungsten is obtained by pressing technology, and sintered for 2 to 4 hours to obtain a rhenium-tungsten thin layer;
[0029] The rhenium-tungsten thin layer is mixed with the graphene nanosheet and ground in a device protected by an inert gas; the powder is placed in an aluminum mold and rotated and pressed for 2 to 3 minutes, and dense ultrafine-grained rhenium-tungsten / graphene powder is obtained by friction heat input and deformation drive.
[0030] Preferably, the purity of the tungsten powder is 99.95%, and the purity of the rhenium powder is 99.98%.
[0031] Preferably, the mass ratio of the tungsten powder to the rhenium powder is 1:(0.11-0.42).
[0032] Preferably, the sintering temperature is 1200-1500° C., and the sintering pressure is 20-50 MPa.
[0033] Preferably, the mass ratio of the nano-rhenium-tungsten thin layer to the graphene nano-sheet is 1:(0.012-0.016).
[0034] Preferably, the grinding speed is 200 rpm, the grinding time is 10 to 12 hours, and the rotary pressing speed is 1000 rpm.
[0035] Preferably, the mass ratio of acetone to N,N-dimethylformamide is 1:(0.2-0.3), and the solvents used in the washing treatment are ether and water, respectively.
[0036] Preferably, the mass ratio of the tungsten complex to 2,11-dimethyldodecane-3,10-diol, triphenylphosphine, 2,2'-di(diethylamino)diethylphosphine and tetrahydrofuran is 1:(0.4-0.5):(0.38-0.4):(0.34-0.36):(1.8-2).
[0037] Preferably, the solvent used for washing is anhydrous ethanol, sodium hydroxide, and deionized water to remove unpolymerized free substances and oligomers.
[0038] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0039] (1) The present invention synthesizes a new compound, methyl 3-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione, which is obtained from ethyl acetoacetate as a starting material through esterification, Knoevenagel condensation and other reactions; the compound is structurally characterized by infrared spectroscopy (IR).
[0040] The present invention synthesizes a brand-new metal-polymer coordination polymer: methyl 3-5-(1,8-naphthyridine-2-yl)-2H-pyrrole-2,4(3H)-dione is coordinated with an ultrafine grain tungsten base to obtain a metal complex, which is then catalyzed and polymerized with 2,11-dimethyldodecane-3,10-diol to obtain an ultrafine grain tungsten base composite material.
[0041] (2) The ultrafine-grained tungsten-based composite material prepared by the present invention has excellent self-healing properties. The composite material relies on the inherent self-healing mechanism of supramolecular interactions such as dynamic bonds, ionic interactions, π-π stacking, metal-ligand interactions, and host-guest interactions inherent in high molecular polymers to achieve autonomous healing. The supramolecular interaction force is very weak, and the non-covalent bonds between polymer chains break when the material is mechanically damaged. These bonds can easily reorganize with each other after being broken, thereby achieving autonomous repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is the infrared absorption (IR) spectrum of the ultrafine-grained tungsten-based composite material prepared in Example 4.
[0043] Figure 2 This is a scanning electron microscope (SEM) image of the ultrafine-grained tungsten-based composite material prepared in Example 4.
[0044] Figure 3 This is a scanning electron microscope (SEM) image of the polymer material prepared in Comparative Example 1.
[0045] Figure 4 This is a scanning electron microscope (SEM) image of the ultrafine-grained tungsten-based composite material prepared in Comparative Example 2.
[0046] Figure 5 This is a scanning electron microscope (SEM) image of the ultrafine-grained tungsten-based composite material prepared in Comparative Example 3.
[0047] Figure 6 Schematic diagram of cutting damage in the initial state of the materials prepared in Example 4 and Comparative Examples 1-3.
[0048] Figure 7 This is the self-repairing condition of the ultrafine-grained tungsten-based composite material prepared in Example 4.
[0049] Figure 8 This is the self-repairing condition of the polymer material prepared in Comparative Example 1.
[0050] Fig. 9 This is the self-repairing condition of the ultrafine-grained tungsten-based composite material prepared in Comparative Example 2.
[0051] Fig.10 This is the self-repairing condition of the ultrafine-grained tungsten-based composite material prepared in Comparative Example 3. DETAILED DESCRIPTION
[0052] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.
[0053] Example 1
[0054] A method for preparing an ultrafine grain tungsten-based composite material comprises the following steps:
[0055] (1) Accurately weigh 5 g of tungsten powder and 0.55 g of rhenium powder, mix them evenly, place them in a mold coated with a release agent, and debug the equipment for pressing; the pressed alloy is sintered at 1200-1500°C and 20-50 MPa for 2-4 h to obtain an ultrafine grain rhenium-tungsten thin layer.
[0056] (2) 5 g of rhenium-tungsten thin layer was mixed with 0.06 g of graphene nanosheets, placed in a device protected by inert gas, and ground at a speed of 200 rpm for 10 to 12 hours; then the powder was placed in an aluminum mold and rotationally pressed at a speed of 1000 rpm for 2 to 3 minutes, and dense ultrafine-grained rhenium-tungsten / graphene nanomaterials were obtained by frictional heat input and deformation drive.
[0057] (3) Accurately weigh 5 g of ethyl acetoacetate and 6.5 g of sodium nitrate into a round-bottom flask, add 9.5 mL of acetic acid to dissolve, and reflux in an oil bath at 115-120° C. for 6-8 h. Monitor the reaction by TLC until it is complete. After the system is cooled to room temperature, filter under reduced pressure to obtain a solid product, wash with water, and dry in an oven to obtain 2-nitro-ethyl acetoacetate with a yield of 86.3%.
[0058] (4) Accurately weigh 5 g of ethyl 2-nitro-acetoacetate, 1.5 g of zinc powder, and 3.45 mL of propionic anhydride into a round-bottom flask, add 13 mL of anhydrous ethanol to dissolve, reflux at 115-120° C. for 8-10 h, monitor the reaction completion by TLC, cool to room temperature, and filter under reduced pressure to obtain a crude product. After drying, recrystallize with hot ethyl acetate, filter while hot, retain the filtrate, and spin dry the solvent to obtain pure ethyl 3-oxo-2-propionamidobutyrate with a yield of 78.4%.
[0059] (5) Accurately weigh 5 g of ethyl 3-oxo-2-propionamidobutyrate, 3 g of 2-aminonicotinaldehyde, and 0.15 mL of pyrrolidine into a round-bottom flask, add 9.5 mL of anhydrous ethanol to dissolve, and reflux at 70-80° C. for 12-14 h. The reaction is complete after TLC monitoring to obtain a crude product. A mobile phase of dichloromethane:methanol in a ratio of 20:1 is used, and column chromatography is performed to obtain pure 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionic acid methyl ester with a yield of 67.3%.
[0060] (6) Accurately weigh 5 g of methyl 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionate, 3 g of titanium tetrachloride, and 0.3 g of triethylsilane into a round-bottom flask, add 9.8 mL of dichloromethane to dissolve, reflux at 25-40° C. for 10-12 h, and monitor the reaction completion by TLC. The obtained crude product is recrystallized from methanol, placed in a refrigerator at 4° C. overnight, filtered, and the solid is immediately rinsed with water to obtain a pure crude 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione product with a yield of 88.4%.
[0061] (7) Accurately weigh 5 g of 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione, 0.85 g of anhydrous lithium chloride, and 3.75 g of ultrafine grain rhenium-tungsten / graphene and place them in a round-bottom flask, add 21 mL of N,N-dimethylformamide to dissolve, and reflux at 150-160° C. for 8-10 h. If there is no undissolved solid in the system, the reaction is complete. Add 105 mL of acetone to the system, refrigerate the flask at below 0° C. overnight, wait for crystals to precipitate, and filter under reduced pressure to obtain a crude product. Rinse with ether and water several times, respectively, to obtain 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione-tungsten complex with a yield of 86.2%.
[0062] (8) Accurately weigh 5 g of the complex, 2 g of 2,11-dimethyldodecane-3,10-diol, 1.9 g of triphenylphosphine, and 1.7 g of 2,2'-di(diethylamino)diethylphosphine into a round-bottom flask, add 8.4 mL of tetrahydrofuran to dissolve, and stir at room temperature for 12 h. The resulting polymer is rinsed with anhydrous ethanol, sodium hydroxide solution, and deionized water to obtain an ultrafine-grained tungsten-based composite material.
[0063] Example 2
[0064] A method for preparing an ultrafine grain tungsten-based composite material comprises the following steps:
[0065] (1) Accurately weigh 5 g of tungsten powder and 2.1 g of rhenium powder, mix them evenly, place them in a mold coated with a release agent, and debug the equipment for pressing; the pressed alloy is sintered at 1200-1500°C and 20-50 MPa for 2-4 h to obtain an ultrafine grain rhenium-tungsten thin layer.
[0066] (2) 5 g of rhenium-tungsten thin layer was mixed with 0.08 g of graphene nanosheets, placed in a device protected by inert gas, and ground at a speed of 200 rpm for 10 to 12 hours; then the powder was placed in an aluminum mold and rotationally pressed at a speed of 1000 rpm for 2 to 3 minutes, and dense ultrafine-grained rhenium-tungsten / graphene nanomaterials were obtained by frictional heat input and deformation drive.
[0067] (3) Accurately weigh 5 g of ethyl acetoacetate and 7 g of sodium nitrate and place them in a round-bottom flask. Add 14.3 mL of acetic acid to dissolve the mixture. Reflux the mixture in an oil bath at 115-120° C. for 6-8 h. Monitor the reaction by TLC until it is complete. After the system is cooled to room temperature, filter the solid product under reduced pressure and dry it in an oven to obtain 2-nitro-ethyl acetoacetate with a yield of 86.4%.
[0068] (4) Accurately weigh 5 g of ethyl 2-nitro-acetoacetate, 1 g of zinc powder, and 3.9 mL of propionic anhydride into a round-bottom flask, add 19 mL of anhydrous ethanol to dissolve, reflux at 115-120° C. for 8-10 h, monitor the reaction completion by TLC, cool to room temperature, and filter under reduced pressure to obtain a crude product. After drying, recrystallize with hot ethyl acetate, filter while hot, retain the filtrate, and spin dry the solvent to obtain pure 3-oxo-2-propionamidobutyric acid ethyl ester with a yield of 66.7%.
[0069] (5) Accurately weigh 5 g of ethyl 3-oxo-2-propionamidobutyrate, 3.5 g of 2-aminonicotinaldehyde, and 0.2 mL of pyrrolidine into a round-bottom flask, add 10 mL of anhydrous ethanol to dissolve, and reflux at 70 to 80° C. for 12 to 14 h. The reaction is complete after monitoring by TLC to obtain a crude product. A mobile phase of dichloromethane:methanol in a ratio of 20:1 is used, and column chromatography is performed to obtain pure 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionic acid methyl ester with a yield of 41.2%.
[0070] (6) Accurately weigh 5 g of methyl 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionate, 3.5 g of titanium tetrachloride, and 1.5 g of triethylsilane into a round-bottom flask, add 19 mL of dichloromethane to dissolve, reflux at 25-40° C. for 10-12 h, and monitor the reaction completion by TLC. The obtained crude product is recrystallized from methanol, placed in a refrigerator at 4° C. overnight, filtered, and the solid is rinsed with water to obtain a pure crude 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione product with a yield of 57.6%.
[0071] (7) Accurately weigh 5 g of 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione, 0.9 g of anhydrous lithium chloride, and 3.9 g of ultrafine grain rhenium-tungsten / graphene into a round-bottom flask, add 26.5 mL of N,N-dimethylformamide to dissolve, and reflux at 150-160° C. for 8-10 h. If there is no undissolved solid in the system, the reaction is complete. Add 105 mL of acetone to the system, refrigerate the flask at below 0° C. overnight, wait for crystals to precipitate, and filter under reduced pressure to obtain a crude product. Rinse with ether and water several times, respectively, to obtain 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione-tungsten complex with a yield of 57.7%.
[0072] (8) Accurately weigh 5 g of the complex, 2.5 g of 2,11-dimethyldodecane-3,10-diol, 2 g of triphenylphosphine, and 1.8 g of 2,2'-di(diethylamino)diethylphosphine into a round-bottom flask, add 11.2 mL of tetrahydrofuran to dissolve, and stir at room temperature for 12 h. The resulting polymer is rinsed with anhydrous ethanol, sodium hydroxide solution, and deionized water to obtain an ultrafine-grained tungsten-based composite material.
[0073] Example 3
[0074] A method for preparing an ultrafine grain tungsten-based composite material comprises the following steps:
[0075] (1) Accurately weigh 5 g of tungsten powder and 1.75 g of rhenium powder, mix them evenly, place them in a mold coated with a release agent, and debug the equipment for pressing; the pressed alloy is sintered at 1200-1500°C and 20-50 MPa for 2-4 h to obtain an ultrafine grain rhenium-tungsten thin layer.
[0076] (2) 5 g of rhenium-tungsten thin layer was mixed with 0.07 g of graphene nanosheets, placed in a device protected by inert gas, and ground at a speed of 200 rpm for 10 to 12 hours; then the powder was placed in an aluminum mold and rotationally pressed at a speed of 1000 rpm for 2 to 3 minutes, and dense ultrafine-grained rhenium-tungsten / graphene nanomaterials were obtained by frictional heat input and deformation drive.
[0077] (3) Accurately weigh 5 g of ethyl acetoacetate and 6.75 g of sodium nitrate into a round-bottom flask, add 12 mL of acetic acid to dissolve, and reflux in an oil bath at 115-120° C. for 6-8 h. Monitor the reaction by TLC until it is complete. After the system is cooled to room temperature, filter under reduced pressure to obtain a solid product, wash with water, and dry in an oven to obtain 2-nitro-ethyl acetoacetate with a yield of 75.3%.
[0078] (4) Accurately weigh 5 g of ethyl 2-nitro-acetoacetate, 3 g of zinc powder, and 3.7 mL of propionic anhydride into a round-bottom flask, add 15.8 mL of anhydrous ethanol to dissolve, reflux at 115-120° C. for 8-10 h, monitor the reaction completion by TLC, cool to room temperature, and filter under reduced pressure to obtain a crude product. After drying, recrystallize with hot ethyl acetate, filter while hot, retain the filtrate, and spin dry the solvent to obtain pure 3-oxo-2-propionamidobutyric acid ethyl ester with a yield of 68.3%.
[0079] (5) Accurately weigh 5 g of ethyl 3-oxo-2-propionamidobutyrate, 3.25 g of 2-aminonicotinaldehyde, and 0.17 mL of pyrrolidine into a round-bottom flask, add 9.8 mL of anhydrous ethanol to dissolve, and reflux at 70-80° C. for 12-14 h. The reaction is complete after monitoring by TLC to obtain a crude product. A mobile phase of dichloromethane:methanol in a ratio of 20:1 is used, and column chromatography is performed to obtain pure 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionic acid methyl ester with a yield of 44.5%.
[0080] (6) Accurately weigh 5 g of methyl 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionate, 3.25 g of titanium tetrachloride, and 0.6 g of triethylsilane into a round-bottom flask, add 10.5 mL of dichloromethane to dissolve, reflux at 25-40° C. for 10-12 h, and monitor the reaction completion by TLC. The obtained crude product is recrystallized from methanol, placed in a refrigerator at 4° C. overnight, filtered, and the solid is rinsed with water to obtain a pure crude 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione product with a yield of 62.6%.
[0081] (7) Accurately weigh 5 g of 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione, 0.87 g of anhydrous lithium chloride, and 3.8 g of ultrafine grain rhenium-tungsten / graphene into a round-bottom flask, add 23.8 mL of N,N-dimethylformamide to dissolve, and reflux at 150-160° C. for 8-10 h. If there is no undissolved solid in the system, the reaction is complete. Add 105 mL of acetone to the system, refrigerate the flask at below 0° C. overnight, wait for crystals to precipitate, and filter under reduced pressure to obtain a crude product. Rinse with ether and water several times, respectively, to obtain 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione-tungsten complex with a yield of 60.8%.
[0082] (8) Accurately weigh 5 g of the complex, 1.75 g of 2,11-dimethyldodecane-3,10-diol, 1.9 g of triphenylphosphine, and 1.75 g of 2,2'-di(diethylamino)diethylphosphine into a round-bottom flask, add 10.7 mL of tetrahydrofuran to dissolve, and stir at room temperature for 12 h. The resulting polymer is rinsed with anhydrous ethanol, sodium hydroxide solution, and deionized water to obtain an ultrafine-grained tungsten-based composite material.
[0083] Example 4
[0084] A method for preparing an ultrafine grain tungsten-based composite material comprises the following steps:
[0085] (1) Accurately weigh 5 g of tungsten powder and 1.25 g of rhenium powder, mix them evenly, place them in a mold coated with a release agent, and debug the equipment for pressing; the pressed alloy is sintered at 1200-1500°C and 20-50 MPa for 2-4 h to obtain an ultrafine grain rhenium-tungsten thin layer.
[0086] (2) 5 g of rhenium-tungsten thin layer was mixed with 0.065 g of graphene nanosheets, placed in a device protected by inert gas, and ground at a speed of 200 rpm for 10 to 12 hours; then the powder was placed in an aluminum mold and rotationally pressed at a speed of 1000 rpm for 2 to 3 minutes, and dense ultrafine-grained rhenium-tungsten / graphene nanomaterials were obtained by frictional heat input and deformation drive.
[0087] (3) Accurately weigh 5 g of ethyl acetoacetate and 6.65 g of sodium nitrate into a round-bottom flask, add 11 mL of acetic acid to dissolve, and reflux in an oil bath at 115-120° C. for 6-8 h. The reaction is monitored by TLC until complete. After the system is cooled to room temperature, the solid product is filtered off under reduced pressure and washed with water and dried in an oven to obtain 2-nitro-ethyl acetoacetate with a yield of 68.9%.
[0088] (4) Accurately weigh 5 g of ethyl 2-nitro-acetoacetate, 2 g of zinc powder, and 2.95 mL of propionic anhydride into a round-bottom flask, add 14.6 mL of anhydrous ethanol to dissolve, reflux at 115-120° C. for 8-10 h, monitor the reaction completion by TLC, cool to room temperature, and filter under reduced pressure to obtain a crude product. After drying, recrystallize with hot ethyl acetate, filter while hot, retain the filtrate, and spin dry the solvent to obtain pure ethyl 3-oxo-2-propionamidobutyrate with a yield of 78.4%.
[0089] (5) Accurately weigh 5 g of ethyl 3-oxo-2-propionamidobutyrate, 3.1 g of 2-aminonicotinaldehyde, and 0.16 mL of pyrrolidine into a round-bottom flask, add 9.6 mL of anhydrous ethanol to dissolve, and reflux at 70-80° C. for 12-14 h. The reaction is complete after TLC monitoring to obtain a crude product. A mobile phase of dichloromethane:methanol in a ratio of 20:1 is used, and column chromatography is performed to obtain pure 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionic acid methyl ester with a yield of 62.9%.
[0090] (6) Accurately weigh 5 g of methyl 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionate, 3.1 g of titanium tetrachloride, and 1.1 g of triethylsilane into a round-bottom flask, add 8.7 mL of dichloromethane to dissolve, reflux at 25-40° C. for 10-12 h, and monitor the reaction completion by TLC. The obtained crude product is recrystallized from methanol, placed in a refrigerator at 4° C. overnight, filtered, and the solid is rinsed with water to obtain a pure crude 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione product with a yield of 57.2%.
[0091] (7) Accurately weigh 5 g of 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione, 0.88 g of anhydrous lithium chloride, and 3.8 g of ultrafine grain rhenium-tungsten / graphene into a round-bottom flask, add 22.7 mL of N,N-dimethylformamide to dissolve, and reflux at 150-160° C. for 8-10 h. If there is no undissolved solid in the system, the reaction is complete. Add 105 mL of acetone to the system, refrigerate the flask at below 0° C. overnight, wait for crystals to precipitate, and filter under reduced pressure to obtain a crude product, which is rinsed several times with ether and water, respectively, to obtain 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione-tungsten complex with a yield of 81.3%.
[0092] (8) Accurately weigh 5 g of the complex, 1.8 g of 2,11-dimethyldodecane-3,10-diol, 1.9 g of triphenylphosphine, and 1.72 g of 2,2'-di(diethylamino)diethylphosphine into a round-bottom flask, add 10.2 mL of tetrahydrofuran to dissolve, and stir at room temperature for 12 h. The resulting polymer is rinsed with anhydrous ethanol, sodium hydroxide solution, and deionized water to obtain an ultrafine-grained tungsten-based composite material.
[0093] Comparative Example 1
[0094] A method for preparing an ultrafine-grained tungsten-based composite material, wherein the difference from Example 4 is that rhenium powder is not added in step (1).
[0095] Comparative Example 2
[0096] A method for preparing an ultrafine-grained tungsten-based composite material, wherein the difference from Example 4 is that no graphene nanosheets are added in step (2).
[0097] Comparative Example 3
[0098] A method for preparing an ultrafine-grained tungsten-based composite material, wherein the difference from Example 4 is that rhenium powder is not added in step (1), and graphene nanosheets are not added in step (2).
[0099] Structural characterization: The ultrafine grain tungsten-based composite materials prepared in Example 4 and Comparative Examples 1 to 3 were characterized by infrared spectroscopy. Figure 1 As shown: the peak at 647μm is the metal-metal interaction between tungsten and rhenium, the peak at 784μm is the metal coordination bond between tungsten and carbon, the peak at 940μm is the metal coordination bond between tungsten and nitrogen, the peak at 1095μm is the bending vibration of the straight-chain COC in the complex, the peak at 1244μm is the bending vibration of the CH on the straight-chain alkyl, the peak at 1304μm is the in-plane and out-of-plane swinging bond and out-of-plane bending vibration of the CH on the benzene ring, the peak at 1342μm is the stretching vibration of the CN bond on the pyrrole ring, the peak at 1463μm is the stretching vibration of the benzene ring skeleton, the peak at 1547μm is the stretching vibration of the imine group (NH) in the pyrrole ring, the peaks at 2864-2974μm are the stretching vibration of the conjugated C=C double bond and the stretching vibration of the carbonyl group (C=O) on the naphthyridine ring, and the peak at 3441μm is the stretching vibration of the CH bond on the aromatic ring and the CH bond stretching vibration on the methylene (CH2) or methyl (CH3)
[0100] In Comparative Example 1, there is no doping of metal rhenium in the complex, so there is no metal-metal interaction peak between rhenium and tungsten in the infrared spectrum, there is a peak of tungsten and carbon metal coordination bond at 832μm, and there is a peak of tungsten and nitrogen metal coordination bond at 948μm; in Comparative Example 2, there is no doping of nanographene in the complex, so there is no tungsten and carbon coordination bond, and there is a peak at 647μm produced by the same metal-metal interaction as in Example 4; in Comparative Example 3, the complex is not doped, and there is a peak at 955μm produced by the coordination of tungsten and nitrogen.
[0101] Performance Test:
[0102] (1) The prepared ultrafine-grained tungsten-based composite material was photographed using a scanning electron microscope (SEM) to observe the density of the material; the denser the material, the better the self-healing performance.
[0103] (2) Self-healing test: The prepared sample was cut and damaged, and the morphological changes during the self-healing process were observed (SEM).
[0104] according to Figure 3-7From the morphology of the ultrafine-grained tungsten-based composite materials prepared by Example 4 and Comparative Examples 2-4 and the polymer material prepared by Comparative Example 1 under an electron microscope, it can be seen that the tungsten-based polymer composite materials modified with rhenium and graphene nanosheets have a higher density and a smooth and delicate surface; the polymer materials lacking rhenium metal and / or graphene doping and the tungsten-based polymer composite materials lacking rhenium or graphene nanosheets have voids of varying sizes and uneven distribution on the surface, a low degree of density, and are loose and porous as a whole, which hinders the interaction of non-covalent bonds of the polymer, thereby hindering the self-repair of the material.
[0105] according to Figure 6 As shown, cutting damage was set on the surface of the prepared material, and Example 4 and Comparative Examples 1-4 were placed in the same environment (constant temperature 100°C) for 30 minutes. The experimental results are shown in Figure 7-10 As shown, the cutting damage of Example 4 was completely healed after 30 minutes, while the damage of Comparative Examples 1-3 was not completely healed after 30 minutes. The width of the cutting damage of Comparative Example 1 was 3.946 microns, that of Comparative Example 2 was 4.380 microns, and that of Comparative Example 3 was 4.644 microns, that is, the influence of the doping components on the self-healing properties of the tungsten-based composite material was metal>non-metal.
[0106] In summary, the material after methyl 3-5-(1,8-naphthyridine-2-yl)-2H-pyrrole-2,4(3H)-dione coordinated with tungsten has excellent self-healing properties. Rhenium and graphene are co-doped to enable tungsten to obtain ultrafine grains with superior grain size. When coordinated with methyl 3-5-(1,8-naphthyridine-2-yl)-2H-pyrrole-2,4(3H)-dione, a dense metal polymer coordination polymer is obtained, which can achieve self-healing of mechanical damage of the material in a short time.
[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An ultrafine grain tungsten-based composite material, characterized in that: Its structural formula is as follows: In the structure, α is an integer between 1 and 10, β is an integer between 1 and 10, and n is an integer between 2 and 12.
2. The method for preparing an ultrafine grain tungsten-based composite material according to claim 1, characterized in that: include: Using ethyl acetoacetate as the starting material, mix it with sodium nitrate and acetic acid, and react at 115-120°C for 6-8h to obtain ethyl acetoacetate; 2-nitro-ethyl acetoacetate is mixed with zinc powder, propionic anhydride and acetic acid, and reacted at 115-120°C for 8-10 hours to obtain a crude product of ethyl 3-oxo-2-propionamidobutyrate, and a pure product is obtained after recrystallization; 3-Oxo-2-propionamidobutyric acid ethyl ester is mixed with 2-aminonicotinaldehyde, pyrrolidine and anhydrous ethanol, and reacted at 70-80°C for 12-14 hours to obtain a crude product of 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionic acid methyl ester, and a pure product is obtained by column chromatography; 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionic acid methyl ester is mixed with titanium tetrachloride, triethylsilane and dichloromethane, and reacted at 25-40° C. for 10-12 hours to obtain a crude product of 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione, the solvent is removed, and the product is dried and recrystallized to obtain a pure product; 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione is mixed with anhydrous lithium chloride, ultrafine grain rhenium-tungsten / graphene, and N,N-dimethylformamide, and reacted at 150-160° C. for 8-10 hours. Acetone is added to the system, and the system is refrigerated overnight below 0° C. to wait for crystals to precipitate, thereby obtaining a crude product of 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione / tungsten complex, which is then washed to obtain a pure product. The tungsten complex was mixed with 2,11-dimethyldodecane-3,10-diol, triphenylphosphine, 2,2'-di(diethylamino)diethylphosphine and tetrahydrofuran, and reacted at room temperature for 12 hours. The obtained high molecular polymer was washed to obtain a tungsten-based composite material.
3. The method for preparing an ultrafine grain tungsten-based composite material according to claim 2, characterized in that: The mass ratio of ethyl acetoacetate, sodium nitrate and acetic acid is 1:(1.3-1.4):(2-3).
4. The method for preparing an ultrafine grain tungsten-based composite material according to claim 2, characterized in that: The mass ratio of the 2-nitro-ethyl acetoacetate to zinc powder, propionic anhydride and acetic acid is 1:(0.3-1):(0.7-0.8):(2-3); the recrystallization reagent is any one or more of ethanol, methanol, ethyl acetate, dichloromethane, ether and chloroform.
5. The method for preparing an ultrafine grain tungsten-based composite material according to claim 2, characterized in that: The mass ratio of 3-oxo-2-propionamidobutyric acid ethyl ester to 2-aminonicotinaldehyde, pyrrolidine and anhydrous ethanol is 1:(0.6-0.7):(0.025-0.034):(1.5-1.6); the mobile phase used for the column chromatography is a dichloromethane and methanol system, and the volume ratio of the two is 20:
1.
6. The method for preparing an ultrafine grain tungsten-based composite material according to claim 2, characterized in that: The mass ratio of the 3-(1,8-naphthyridin-2-yl)-3-propionamidopropionic acid methyl ester to titanium tetrachloride, triethylsilane and dichloromethane is 1:(0.6-0.7):(0.06-0.3):(2.6-3); the recrystallization solvent is any one or more of ethanol, methanol, ethyl acetate and acetone.
7. The method for preparing an ultrafine grain tungsten-based composite material according to claim 2, characterized in that: The mass ratio of the 3-methyl-5-(1,8-naphthyridin-2-yl)-2H-pyrrole-2,4(3H)-dione to LiCl, ultrafine grain rhenium-tungsten / graphene, and N,N-dimethylformamide is 1:(0.17-0.18):(0.75-0.78):(4-5); the mass ratio of acetone to N,N-dimethylformamide is 1:(0.2-0.3); and the solvents used in the washing treatment are ether and water, respectively.
8. The method for preparing an ultrafine grain tungsten-based composite material according to claim 2, characterized in that: The method for preparing the ultrafine grain rhenium-tungsten / graphene powder comprises: The tungsten powder and rhenium powder are mixed evenly, and rhenium-doped nano-tungsten is obtained by pressing technology, and sintered for 2 to 4 hours to obtain a rhenium-tungsten thin layer; The rhenium-tungsten thin layer is mixed with the graphene nanosheet and ground in a device protected by an inert gas; the powder is placed in an aluminum mold and rotated and pressed for 2 to 3 minutes, and dense ultrafine-grained rhenium-tungsten / graphene powder is obtained by friction heat input and deformation drive.
9. The method for preparing an ultrafine grain tungsten-based composite material according to claim 8, characterized in that: The purity of the tungsten powder is 99.95%, the purity of the rhenium powder is 99.98%, and the mass ratio of tungsten powder to rhenium powder is 1:(0.11-0.42); the sintering temperature is 1200-1500°C, and the sintering pressure is 20-50MPa; the mass ratio of the nano-rhenium-tungsten thin layer to the graphene nanosheet is 1:(0.012-0.016), the grinding speed is 200rpm, the grinding time is 10-12h, and the rotary pressing speed is 1000rpm.
10. The method for preparing an ultrafine grain tungsten-based composite material according to claim 2, characterized in that: The mass ratio of the tungsten complex to 2,11-dimethyldodecane-3,10-diol, triphenylphosphine, 2,2'-bis(diethylamino)diethylphosphine and tetrahydrofuran is 1:(0.4-0.5):(0.38-0.4):(0.34-0.36):(1.8-2); The washing solvents are anhydrous ethanol, sodium hydroxide and deionized water.
Citation Information
Patent Citations
Ultra-fine grain TiC and Y2O3 doped W-based composite and preparation method thereof
CN107326240A
Method for preparing grain-size-contrdlable superfine crystallite tungsten and tungsten-copper composite material
CN1775425A